2018
DOI: 10.1007/s11064-018-2586-8
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Boosts Cognitive Function by Targeting SIRT1

Abstract: Cognitive decline is among the most devastating age-related conditions and is rapidly becoming an important cause of disease burdens worldwide. New strategies for the prevention and management of cognitive decline are needed. Resveratrol, a polyphenolic compound, has been found to enhance brain health through multiple signaling pathways. Optimal SIRT1 activation is the most crucial step in the neuroprotection provided by resveratrol against cognitive impairment. This review discusses several recent development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…One of the most relevant examples is resveratrol, shown to have neuroprotective properties by decreasing microglia-induced neuroinflammation, protecting the brain against hypoxic-ischemic damage and ameliorating cognitive function in the Alzheimer's disease model [38][39][40]52]. It also seems to decrease age-related cognitive decline and increase cognitive function through SIRT1 modulation that, among other important functions, seems to modulate the growth of dendrites and axons [53]. The neuroprotective effects of resveratrol go beyond the central nervous system, since it also seemed to reduce NFκB-mediated neuroinflammation and endoplasmic reticulum stress in an ischemia-reperfusion model of vasculitis peripheral neuropathy; this condition arises from an obstruction in the blood vessels supplying peripheral nerves due to inflammation and may be related to neuropathic pain [54].…”
Section: Beneficial Effects Of Polyphenols and Neuroprotectionmentioning
confidence: 99%
“…One of the most relevant examples is resveratrol, shown to have neuroprotective properties by decreasing microglia-induced neuroinflammation, protecting the brain against hypoxic-ischemic damage and ameliorating cognitive function in the Alzheimer's disease model [38][39][40]52]. It also seems to decrease age-related cognitive decline and increase cognitive function through SIRT1 modulation that, among other important functions, seems to modulate the growth of dendrites and axons [53]. The neuroprotective effects of resveratrol go beyond the central nervous system, since it also seemed to reduce NFκB-mediated neuroinflammation and endoplasmic reticulum stress in an ischemia-reperfusion model of vasculitis peripheral neuropathy; this condition arises from an obstruction in the blood vessels supplying peripheral nerves due to inflammation and may be related to neuropathic pain [54].…”
Section: Beneficial Effects Of Polyphenols and Neuroprotectionmentioning
confidence: 99%
“…Among others, epigenetic mechanisms seem to play a relevant role [26,27]. In this regard, neuroprotective properties of other polyphenols have been associated to the NAD-dependent histone deacetylase, sirtuin 1 (SIRT1) protein; since this protein shows a marked age-related reduction in brain, mainly in the hippocampus [6,25,28]. However, the effect of green tea extract on this protein has not been investigated deeply, at least in vivo with a focus on the brain [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is one of compounds to slow aging. Studies have shown that resveratrol attenuates hydrogen peroxide-induced aging by upregulating autophagy in human umbilical vein endothelial cells (Du et al, 2019 antiinflammatory, antiapoptotic processes, and autophagy regulation, as well as increases in cerebral blood flow and improvements in the plasticity of synaptic pathways (Cao et al, 2018). However, the mechanism of its pharmacological action has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%